(untitled) (Global Journal of Human-Social Science, 2023)
Quite recently I wrote that A M Hocart is a very little known British anthropologist Korsbaek in press which is true But if that is so the British anthropologist Gunnar Landtman born in Finland is absolutely unknown at least in the Spanish speaking world And that in spite of the fact that he is of a certain importance at least in the anthropological universe